Kinetics of thermal dewaxing of injection‐molded silicon carbide. Issue 2 (25th July 2019) - Chinn, Richard E.; Enneti, Ravi K.; Kate, Kunal H.; Atre, Sundar V.
Abstract : The kinetics of thermally dewaxed silicon carbide (SiC) mono‐ and bimodal injection molding feedstocks by three models were compared to solvent‐dewaxed SiC and thermally dewaxed powders from other studies. The E a of pyrolytic dewaxing was graphically estimated by the master dewaxing curve model as ~80 kJ/mol for monomodal and ~60 kJ/mol for bimodal SiC powder size distributions, a little higher than the ~50 kJ/mol by solvent dewaxing of the same compositions. The nanoparticles in the bimodal feedstock did not change the mechanism of wax decomposition, but may have lowered the thermal Ea with additional nucleation sites. Abstract: Powder injection molding is a near‐net shape, high‐speed fabrication process that has been studied only lightly with silicon carbide (SiC) as the powder. The addition of nanoparticles to the monomodal powder to form a bimodal powder increases the solid fraction in the feedstock but may also adversely affect other properties. In this paper, the kinetic properties of thermally dewaxed SiC mono‐ and bimodal feedstocks by three models were compared to solvent‐dewaxed SiC and thermally dewaxed powder metal from other studies. The activation energy E a of pyrolytic dewaxing was graphically estimated by the master dewaxing curve model as ~80 kJ/mol for monomodal and ~60 kJ/mol for bimodal SiC powder size distributions, a little higher than the ~50 kJ/mol by solvent dewaxing of the same compositions. The E a in the Flynn‐Wall model was 64 kJ/mol for monomodal and 53 kJ/mol for bimodal. The E a was 49 kJ/mol for monomodal and 42 kJ/mol for bimodal SiC powder by the Kissinger thermal analysis model. The lower E a of the bimodal feedstock was attributed to its increased nucleation sites. These results provide the basis for dewaxing models—part of the rate‐limiting step in powder injection molding—for SiC powder‐binder systems.